Moral luck and moral equality of opportunity - Crisp, R (Oxford University Press, 2017)
This paper concerns the problem of moral luck—the fact that our moral judgements appear to depend, perhaps unjustifiably, on matters of luck. The history and scope of the problem are discussed. It is suggested that our result-sensitive sentiments have their origin in views about moral pollution we might now wish to reject in favour of a volitionalist ethics.